IMPLEMENTASI HUKUM INTERNASIONAL TERHADAP KEJAHATAN GENOSIDA PADA ETNIS ROHINGYA - Ilhamda Fattah Kaloko; Eno Prasetiawan; Mustika Sukma Utari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Humanitarian law is a set of rules based on international treaties and international customs that limit the powers of belligerent parties to use the means and means of war to defeat the enemy and regulate the protection of war. International humanitarian law is closely related to human rights (hereinafter referred to as human rights), both of which concern the right to protection and the existence of human beings that must be guarded and protected when related to threats of violence and violations that occur to humans when war occurs. Problems regarding human rights violations are related to the protection of human dignity from crimes, especially international crimes that are cruel and have a broad impact on humanity. The formulation of the research problem: 1) The crime of genocide that occurred against the Rohingya ethnicity in the perspective of international criminal law? 2) Accountability for the crime of genocide against the Rohingya? Research conclusions: 1) If a crime does not contain an international dimension, then there is the main condition, namely the touch of universal human values, legal awareness and a sense of justice for mankind. Although there is no international dimension in it, but the incident can be said to be an international crime because it caused reactions, sympathy, and condemnation by the entire international community for such heinous and inhumane acts. 2) The responsibility for all inhumane treatment of the Rohingya Ethnic, seen from the Rome Statute setting regarding individual and command responsibility can be punished. The responsibility in the ICC is that the Court adheres to individual criminal responsibility (Individual Criminal Responsibility) which in Article 25 paragraph (1) of the Court's jurisdiction is over persons or individuals who must be responsible for the crimes they have committed as stipulated in the ICC Statute.